Uterine sarcoma: a clinical case and a literature review - Bužinskienė, Diana; Mikėnas, Saulius; Drąsutienė, Gražina; Mongirdas, Matas (Acta medica Lituanica, 2019)
Background. Uterine sarcomas are rare gynaecologic tumours representing 3–7% of all uterine malignancies. The aetiology of sarcomas is still unclear: it is thought, that chromosomal translocations have influence on wide histological variety of sarcomas. Presenting symptoms are vague and nonspecific. Usually sarcoma causes abnormal vaginal bleeding, can cause abdominal or pelvic pain, or manifests as a rapidly growing uterine tumour. The diagnosis of sarcoma is often made retrospectively after surgical removal of a presumed benign uterine neoplasm, because imaging modalities such as ultrasound, computed tomography, or magnetic resonance imaging cannot yet accurately and reliably distinguish between benign leiomyoma and malignant pathology. If there are certain clinical features that raise a suspicion of malignancy in the uterus, it is recommended to avoid the use of power morcellation through laparoscopic surgery in order to prevent disease dissemination. Materials and methods. We present a clinical case of a 64-year-old patient, who was referred to hospital due to abdominal pain and tenesmus that lasted for two days. From a past medical history it was known that previously the patient had been diagnosed with uterine myoma. Transvaginal ultrasonography showed a 10.4 cm × 9.8 cm uterine tumour of nonhomogeneous structure with signs of necrosis and good vascularization. The patient refused urgent hysterectomy, that was advised to her. The patient was operated on one month later and total hysterectomy with bilateral salpingooforectomy was performed. Postoperative histological evaluation showed undifferentiated sarcoma uterus pT1b L/V0. Imaging modalities were made to evaluate possible dissemination of the disease. In the absence of signs of disease progression, the patient received radiotherapy and brachytherapy and was followed-up by doctors. Results and conclusions. Uterine sarcomas are highly malignant tumours that originate from smooth muscles and connective tissue elements of the uterus and make up 1% of all malignant gynaecological tumours and about 3–7% of all malignant uterine tumours. Imaging modalities cannot yet reliably distinguish benign myomas from malignant sarcomas. It is important not to damage the wholeness of uterus during operation in order to prevent dissemination of the disease in the abdominal cavity. The low-grade endometrial stromal sarcoma has the best survival prognosis, while carcinosarcoma and undifferentiated uterine sarcoma have the lowest survival rates.